Students’ development of deliberative competences: The contribution of democratic experiences in urban schools - Strijbos, Jetske; Engels, Nadine (Frontiers in Education, 2023)
A democratic school culture has been identified in previous research as a lever for the development of deliberative competences. However, the antecedents of deliberative competence development at school level are less examined. Therefore, this study investigated the impact of student characteristics (age, gender, finality), urban school contexts (location of the school, socioeconomic and cultural characteristics of the student population) and different dimensions of the perceived democratic school culture (fair support, responsibility, co-decision, discussion, acceptance) on students’ mastery of three deliberative competences: tolerance, curiosity, and empathy. A multilevel analysis of a survey, completed by 5165 Dutch-speaking Belgian secondary school students, revealed the importance of the perceived fair support from teachers, opportunities to discuss, and acceptance by peers at school for the mastery of deliberative competences. Furthermore, urban schools were discovered to be strong negative predictors of all three competences, although fair support and discussion opportunities appear to partially compensate for this effect. These results highlight the importance of a democratic school culture, especially in urban schools, for developing empathy, tolerance, and curiosity. Moreover, the detailed results of this study could guide urban school teams in shaping democratic learning environments.